Report from the Sustainable Development Working Group (SDWG) to the SAO meeting in Rovaniemi on 12-13 June 2001. - Sustainable Development Working Group (SDWG) (Arctic Council Secretariat, 2001)
Arctic Council working group Sustainable Development Working Group (SDWG)'s report to SAOs at the Senior Arctic Officials meeting in Rovaniemi, Finland, June 12-13 2001.